Effects of a High Protein Food Supplement on Physical Activity, Motor Performance and Health Related Quality of Life of HIV Infected Botswana Children on Anti-Retroviral Therapy (ART) - Leapetswe Malete; Lucky Mokgatlhe; Maria Nnyepi; Jose Jackson; Fujun Wen; Maurice Bennink; Gabriel Anabwani; Jerry Makhanda; Ibou Thior; Philemon Lyoka; Lorraine Weatherspoon (AIMS Press, 2017)
Objective: Despite existing evidence about the benefits of nutrition, physical activity (PA) and sport to the overall health and wellbeing of children, knowledge gaps remain on this relationship in children living with chronic conditions like HIV/AIDS. Such knowledge should inform context specific programs that could enhance the quality of life of children. The purpose of this study was to examine the effects of integrating a nutrition intervention (culturally tailored food supplement) into antiretroviral therapy (ART) on psychosocial outcomes and physical activity among HIV-positive children in Botswana. Method: 201 HIV-positive children (6-15 years; M = 9.44, SD = 2.40) were recruited and randomly assigned (stratified by age and gender) to two groups. The intervention group (n = 97) received a high protein (bean-sorghum plus micronutrients) food supplement, while the control group (n = 104) received a sorghum plus micronutrients supplement. Participants were followed over 12 months. Anthropometric measures, PA, motor performance, and health related quality of life (HRQL) were collected at baseline, 6 and 12 months. Results: Mixed repeated-measures ANOVA revealed a significant time effect of the food supplement on target variables except body fat percentage, speed, and school functioning. Time×treatment interaction was found for physical functioning, psyioning achosocial functnd total quality of life score. Scores on physical functioning and total of quality life in the intervention group significantly increased from baseline to 6 months compared with the control group (p = 0.015). Conclusion: A combination of ART and nutritional intervention had a positive effect on physical functioning and total quality of life of HIV-positive children in this study. There were also improvements to physical activity and motor performance tests over time. More research is needed on long term effects of nutrition and PA interventions on HRQL in children living with HIV.